An Investigation to Evaluate the Awareness of Obesity and Its Long-term Consequences Among Adolescents from a Chosen Higher Secondary School in Bagalkot - Sanjay Alagundi; Bhairgouda Patil; Chetan Sangati (International Journal of Community Health Nursing And Practices, 2024)
Using descriptive research methodology and a descriptive survey strategy, teenagers from a selected higher secondary school in Bagalkot were asked to rank their awareness of obesity and its long-term implications. To satisfy the objectives of the study and assess teenagers’ knowledge of obesity in light of the nature of the issue, a systematic, self-administered knowledge questionnaire was created. Interaction with guides and experts in the nursing and medical domains verified the tool’s validity and dependability. The purposive sample approach was used to select 100 youths. Data was gathered via an organized knowledge survey. Statistics, both descriptive and inferential, were used to analyze the collected data. For most of the obese population, the survey found that most teenagers have moderate knowledge scores on obesity, with an average score of 16.62. Factors such as family type, age, gender, birth order, religion, income, parents’ occupations, nutrition, and leisure activities significantly correlated with knowledge scores. However, exercise, issues, family history, and personal history of obesity did not significantly correlate.
Keywords: awareness of obesity and its long-term consequences; evaluation; investigation